Composite bipolar membrane as well as preparation method and application thereof

By adopting a composite bipolar membrane, the problems of low efficiency and poor stability in the production of hexacyanocobalt acid are solved, and efficient and stable hexacyanocobalt acid is achieved.

CN119588164AActive Publication Date: 2025-03-11TONGZHOU ZONGHENG (XIAMEN) FLUID TECH CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411791054.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-11
Estimated Expiration
2044-12-06

AI Technical Summary

Technical Problem

The existing bipolar membrane electrodialysis method has low efficiency and poor stability when producing hexacyanocobalt acid, resulting in a significant decrease in the generation efficiency with the prolonged use time.

Method used

A composite bipolar film consisting of cation exchange membranes, MOF transition membranes and anion exchange membranes stacked in sequence are used. The cation exchange membranes and anion exchange membranes are formed of random copolymers with specific structures, and a modified MOF transition membrane is provided therebetween.

Benefits of technology

Through this composite bipolar film, hexacyanocobalt acid can be produced continuously and efficiently, extending the service life of the bipolar film and improving production stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119588164A_ABST
    Figure CN119588164A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of compound preparation, and particularly relates to a composite bipolar membrane and a preparation method and application thereof. The composite bipolar membrane provided by the invention comprises a cation exchange membrane, an MOF (Metal Organic Framework) transition membrane and an anion exchange membrane which are sequentially stacked, the cation exchange membrane is formed by a first polymer, and the first polymer is a random copolymer with a structure as shown in a formula (1); the anion exchange membrane is formed by a second polymer, and the second polymer is a random copolymer with a structure as shown in a formula (2). When the composite bipolar membrane provided by the invention is used for producing the hexacyanocobalt acid by a bipolar membrane electrodialysis method, the hexacyanocobalt acid can be continuously and efficiently obtained, and the application prospect is wide. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of compound preparation, and specifically relates to a composite bipolar membrane and a preparation method and application thereof. Background Art

[0002] The chemical formula of hexacyanocobalt acid is usually H3Co(CN)6, and it has a wide range of uses in the chemical industry, materials science, and biomedicine. In the chemical industry, hexacyanocobalt acid has a wide range of applications in metal surface treatment, catalyst preparation, and synthesis of other organic metal compounds. For example, it can be used as an important raw material for the preparation of cyanide complex catalysts (DMC). In materials science, the special properties of hexacyanocobalt acid make it a key raw material for the manufacture of high-performance materials. For example, it can be used to manufacture conductive materials, magnetic materials, and modifiers for polymer materials. In biomedicine, hexacyanocobalt acid is used as a carrier for certain drugs and biomolecules due to its strong complexing ability and biocompatibility, which helps to improve the targeting and bioavailability of drugs.

[0003] The preparation methods of hexacyanocobalt acid mainly include chemical synthesis and bipolar membrane electrodialysis. The chemical synthesis method includes preparation via copper hexacyanocobaltate and preparation via potassium hexacyanocobaltate. Among them, the preparation process via copper hexacyanocobaltate includes reacting copper hexacyanocobaltate with hydrogen sulfide to obtain hexacyanocobalt acid, or reacting copper hexacyanocobaltate with calcium sulfide or barium sulfide to prepare calcium hexacyanocobaltate or barium hexacyanocobaltate, and then performing a double decomposition reaction of calcium hexacyanocobaltate or barium hexacyanocobaltate with dilute sulfuric acid to obtain hexacyanocobalt acid. The preparation process of potassium hexacyanocobaltate includes introducing hydrogen chloride gas into a saturated solution of potassium hexacyanocobaltate, and hexacyanocobaltate and a small amount of potassium chloride will precipitate at the same time. Since hexacyanocobaltate is soluble in ethanol, ethanol can be added to the precipitate to dissolve the hexacyanocobaltate, and then the dissolution liquid is decompressed to remove the ethanol to obtain hexacyanocobaltate; or hexacyanocobaltate can be prepared by double decomposition reaction of hexacyanocobaltate and sulfuric acid, but the reaction needs to be carried out under acidic conditions, and in order to remove the generated potassium sulfate and potassium hydrogen sulfate as precipitants, a large amount of methanol is required as a solvent. The bipolar membrane electrodialysis method generally includes sending a potassium hexacyanocobaltate aqueous solution and deionized water into the acid and alkaline chambers of a bipolar membrane electrodialysis device respectively and applying electricity for treatment. After electrodialysis, a hexacyanocobaltate solution can be obtained in the acid chamber, and a potassium hydroxide solution can be obtained in the alkaline chamber. Although bipolar membrane electrodialysis has the advantages of low energy consumption, simple operation and easy scale-up compared to chemical synthesis, it cannot efficiently produce hexacyanocobalt acid, and the bipolar membrane has a short life. As the bipolar membrane is used for a longer time, the efficiency of hexacyanocobalt acid production will drop significantly, and the stability is poor. Summary of the invention

[0004] The first object of the present invention is to provide a composite bipolar membrane capable of improving the production efficiency and stability of hexacyanocobaltate.

[0005] The second object of the present invention is to provide a method for preparing the composite bipolar membrane.

[0006] The third object of the present invention is to provide an application of the composite bipolar membrane in the preparation of hexacyanocobaltate.

[0007] Specifically, the composite bipolar membrane provided by the present invention comprises a cation exchange membrane, a MOF transition membrane and an anion exchange membrane stacked in sequence; the cation exchange membrane is formed by a first polymer, which is a random copolymer having a structure shown in formula (1); the anion exchange membrane is formed by a second polymer, which is a random copolymer having a structure shown in formula (2);

[0008]

[0009] m and n represent the molar proportions of the two structural units in formula (1), and the ratio of m to n is 1:(0.5-2); p and q represent the molar proportions of the two structural units in formula (2), and the ratio of p to q is 1:(0.5-2);.

[0010] The method for preparing the composite bipolar membrane provided by the present invention comprises the following steps:

[0011] S21. sodium styrene sulfonate and butadiene are added to an organic solvent at a molar ratio of 1:(0.5-2) to carry out a first copolymerization reaction, and then the obtained sodium styrene sulfonate / butadiene copolymer is subjected to a first thiol-ene click reaction with 2-fluoro-4-mercaptoaniline to obtain a solution containing a first polymer;

[0012] Styrene and butadiene are added into an organic solvent at a molar ratio of 1:(0.5-2) to carry out a second copolymerization reaction, and then the obtained styrene / butadiene copolymer is subjected to a second thiol-ene click reaction with 3-amino-5-mercapto-1,2,4-triazole to obtain a solution containing a second polymer;

[0013] S22. Spray a solution containing the first polymer on the surface of the substrate and dry it to obtain a cation exchange membrane layer; spray a solution containing the modified MOF material on the surface of the cation exchange membrane and dry it to obtain a MOF transition membrane; spray a solution containing the second polymer on the surface of the MOF transition membrane and dry it to obtain an anion exchange membrane.

[0014] The key to the present invention is that the cation exchange membrane is formed by a random copolymer represented by formula (1), and the anion exchange membrane is formed by a random copolymer represented by formula (2), and a MOF transition membrane is arranged between the cation exchange membrane and the anion exchange membrane. The composite bipolar membrane thus obtained can be used for the production of hexacyanocobalt acid by bipolar membrane electrodialysis to obtain hexacyanocobalt acid continuously and efficiently. The reason for this may be that: on the one hand, the MOF material can improve the efficiency of bipolar membrane electrolysis of water, and can provide [Co(CN)6] 3- More H + , which can promote the synthesis of hexacyanocobaltate; on the other hand, the existing bipolar membranes are usually based on aromatic carbon skeletons, but the carbon-oxygen bonds in the aromatic carbon skeletons are easily affected by the OH generated by the bipolar membrane. - The random copolymers shown in formula (1) and formula (2) both have a carbon-carbon double bond main chain and are not easily attacked by OH. - At the same time, the random copolymer having the structure shown in formula (1) has sodium benzenesulfonate groups and fluoroaniline groups evenly distributed on the side chain. As shown in formula (3), the sodium benzenesulfonate groups and fluoroaniline groups are spaced and suspended on the polymer chain. The presence of benzenesulfonic acid groups can promote the electrolysis of water. The presence of fluoroaniline groups can stabilize the chemical bonds of the anode membrane. The random copolymer having the structure shown in formula (2) has phenyl and nitrogen heterocyclic functional groups evenly distributed on the side chain. As shown in formula (4), the phenyl and nitrogen heterocyclic functional groups are spaced and suspended on the polymer chain. The presence of nitrogen heterocyclic functional groups can make the electron distribution of the second polymer more uniform, thereby giving the polymer stronger alkali resistance, making the bipolar membrane more resistant to high concentration OH. - Furthermore, the random copolymers shown in formula (1) and formula (2) have a relatively flexible main chain provided by CC and relatively rigid side chains provided by sodium benzenesulfonate group / fluoroaniline group and phenyl / nitrogen heterocyclic functional group. The flexible main chain can improve the impact resistance of the bipolar membrane, making it have good tolerance to the flow of liquid during use, while the rigid side chain can improve the supporting force, making the bipolar membrane less susceptible to the impact of liquid flow disturbance and affecting the service life.

[0015]

[0016] In formula (3), represent represent

[0017] In formula (4), represent represent

[0018] In a preferred embodiment, the MOF transition membrane is formed by a modified MOF material, and the modified MOF material is a MOF material co-modified with Fe and Cu. In this case, the production efficiency of hexacyanocobaltate can be further improved. It is speculated that the reason may be that iron ions and copper ions can synergistically increase the reactivity of water, weaken molecular bonds, and accelerate the dissociation of water in the middle layer of the bipolar membrane into H + and OH - , thereby promoting the synthesis of hexacyanocobaltate. DETAILED DESCRIPTION

[0019] The composite bipolar membrane provided by the present invention comprises a cation exchange membrane, a MOF transition membrane and an anion exchange membrane stacked in sequence; the cation exchange membrane is formed by a first polymer, which is a random copolymer having a structure shown in formula (1); the anion exchange membrane is formed by a second polymer, which is a random copolymer having a structure shown in formula (2);

[0020]

[0021] m and n represent the molar ratio of the two structural units in formula (1), and the ratio of m to n is 1:(0.5-2), and can be specifically 1:0.5, 1:0.8, 1:1, 1:1.2, 1:1.4, 1:1.6, 1:1.8, 1:2 or any value therebetween. p and q represent the molar ratio of the two structural units in formula (2), and the ratio of p to q is 1:(0.5-2), and can be specifically 1:0.5, 1:0.8, 1:1, 1:1.2, 1:1.4, 1:1.6, 1:1.8, 1:2 or any value therebetween.

[0022] In a preferred embodiment, the thickness of the cation exchange membrane is 10 to 60 microns, specifically 10 microns, 15 microns, 20 microns, 25 microns, 30 microns, 35 microns, 40 microns, 45 microns, 50 microns, 55 microns, 60 microns or any value therebetween; the thickness of the MOF transition membrane is 1 to 10 microns, specifically 1 micron, 2 microns, 4 microns, 6 microns, 8 microns, 10 microns or any value therebetween; the thickness of the anion exchange membrane is 5 to 20 microns, specifically 5 microns, 8 microns, 10 microns, 12 microns, 15 microns, 18 microns, 20 microns or any value therebetween.

[0023] The present invention has no particular limitation on the source of the first polymer, as long as it has the structure shown in formula (1). Formula (1) only represents the specific structure and ratio of each unit, and cannot represent the connection relationship between the structural units. The polymer shown in formula (1) is a random polymer. In a preferred embodiment, the first polymer is prepared according to the following method: sodium styrene sulfonate and butadiene are added into an organic solvent at a molar ratio of 1: (0.5 to 2) to carry out a first copolymerization reaction, and then the obtained sodium styrene sulfonate / butadiene copolymer is subjected to a first thiol-ene click reaction with 2-fluoro-4-mercaptoaniline to obtain a solution containing the first polymer. Wherein, the conditions of the first copolymerization reaction preferably include a polymerization temperature of 50 to 100°C, such as 50°C, 60°C, 70°C, 80°C, 90°C, 100°C or any value therebetween; a polymerization pressure of 0.1 to 0.5 MPa, such as 0.1 MPa, 0.2 MPa, 0.3 MPa, 0.4 MPa, 0.5 MPa or any value therebetween; a polymerization time of 0.5 to 10 h, such as 0.5 h, 1 h, 2 h, 4 h, 6 h, 8 h, 10 h or any value therebetween. The molar ratio of butadiene to 2-fluoro-4-mercaptoaniline is preferably (0.9 to 1.1):1, such as 0.9:1, 0.95:1, 1:1, 1.05:1, 1.1:1 or any value therebetween. The conditions of the first thiol-ene click reaction preferably include a temperature of 70 to 100°C, such as 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C or any value therebetween; a polymerization pressure of 0.1 to 0.5 MPa, such as 0.1 MPa, 0.2 MPa, 0.3 MPa, 0.4 MPa, 0.5 MPa or any value therebetween; and a polymerization time of 0.5 to 5 h, such as 0.5 h, 1 h, 2 h, 4 h, 5 h or any value therebetween.

[0024] The present invention does not specifically limit the source of the second polymer, as long as it has the structure shown in formula (2). Formula (2) only represents the specific structure and ratio of each unit, and cannot represent the connection relationship between the structural units. The polymer shown in formula (2) is a random polymer. In a preferred embodiment, the second polymer is prepared according to the following method: styrene and butadiene are added into an organic solvent at a molar ratio of 1: (0.5 to 2) for a second copolymerization reaction, and then the obtained styrene / butadiene copolymer is subjected to a second thiol-ene click reaction with 3-amino-5-mercapto-1,2,4-triazole to obtain a solution containing the second polymer. Wherein, the conditions of the second copolymerization reaction preferably include a polymerization temperature of 50 to 100°C, such as 50°C, 60°C, 70°C, 80°C, 90°C, 100°C or any value therebetween; a polymerization pressure of 0.1 to 0.5 MPa, such as 0.1 MPa, 0.2 MPa, 0.3 MPa, 0.4 MPa, 0.5 MPa or any value therebetween; a polymerization time of 0.5 to 10 h, such as 0.5 h, 1 h, 2 h, 4 h, 6 h, 8 h, 10 h or any value therebetween. The molar ratio of butadiene to 3-amino-5-mercapto-1,2,4-triazole is preferably (0.9 to 1.1):1, such as 0.9:1, 0.95:1, 1:1, 1.05:1, 1.1:1 or any value therebetween. The conditions of the first thiol-ene click reaction preferably include a temperature of 70 to 100°C, such as 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C or any value therebetween; a polymerization pressure of 0.1 to 0.5 MPa, such as 0.1 MPa, 0.2 MPa, 0.3 MPa, 0.4 MPa, 0.5 MPa or any value therebetween; and a polymerization time of 0.5 to 5 h, such as 0.5 h, 1 h, 2 h, 4 h, 5 h or any value therebetween.

[0025] In the present invention, the terms "first" and "second" are only used to distinguish the same substance and / or condition occurring at different times for the convenience of description, and have no other special meanings. In addition, the pressures are all gauge pressures.

[0026] In the present invention, the MOF transition film can be formed of an unmodified MOF material or a modified MOF material, preferably a modified MOF material. The modified MOF material can be a Fe-modified MOF material, and is particularly preferably a Fe and Cu co-modified MOF material.

[0027] In a preferred embodiment, the Fe and Cu co-modified MOF material is prepared according to the following method: S11. Disperse 3,5-pyrazole dicarboxylic acid in an alkaline solution, add aluminum chloride to the obtained dispersion and stir until dissolved, then heat the obtained solution at 90-110°C for 10-48h and filter, dry the obtained precipitate to obtain a MOF carrier; S12. Activate the MOF carrier at 140-160°C for 10-24h, then disperse the obtained activated MOF carrier with ferric nitrate and copper nitrate in an organic solvent, then heat to 60-80°C for 10-48h, wait for the reaction result and cool to room temperature to obtain a solution containing the modified MOF material. Among them, the mass ratio of the MOF carrier, ferric nitrate and copper nitrate is preferably 1: (0.5-0.8): (0.1-0.3). Specifically, based on 1 part by weight of the MOF carrier, the amount of ferric nitrate is 0.5 to 0.8 parts by weight, such as 0.5, 0.6, 0.7, 0.8 parts by weight or any value therebetween; the amount of copper nitrate is 0.1 to 0.3 parts by weight, such as 0.1, 0.15, 0.2, 0.25, 0.3 parts by weight or any value therebetween.

[0028] The method for preparing the composite bipolar membrane provided by the present invention comprises the following steps:

[0029] S21. sodium styrene sulfonate and butadiene are added to an organic solvent at a molar ratio of 1:(0.5-2) to carry out a first copolymerization reaction, and then the obtained sodium styrene sulfonate / butadiene copolymer is subjected to a first thiol-ene click reaction with 2-fluoro-4-mercaptoaniline to obtain a solution containing a first polymer;

[0030] Styrene and butadiene are added into an organic solvent at a molar ratio of 1:(0.5-2) to carry out a second copolymerization reaction, and then the obtained styrene / butadiene copolymer is subjected to a second thiol-ene click reaction with 3-amino-5-mercapto-1,2,4-triazole to obtain a solution containing a second polymer;

[0031] S22. Spray a solution containing the first polymer on the surface of the substrate and dry it to obtain a cation exchange membrane layer; spray a solution containing the modified MOF material on the surface of the cation exchange membrane and dry it to obtain a MOF transition membrane; spray a solution containing the second polymer on the surface of the MOF transition membrane and dry it to obtain an anion exchange membrane.

[0032] In the preparation process of the above-mentioned composite bipolar membrane, the concentrations of the solution containing the first polymer, the solution containing the second polymer and the solution containing the modified MOF material are preferably each independently 0.1 to 10 wt%, such as 0.1 wt%, 1 wt%, 2 wt%, 4 wt%, 6 wt%, 8 wt%, 10 wt% or any value therebetween.

[0033] In the above-mentioned preparation process of the composite bipolar membrane, the raw materials and conditions of step S21 have been described above and will not be repeated here.

[0034] In the preparation process of the above-mentioned composite bipolar membrane, in step S22, the conditions for drying the solution containing the first polymer, the solution containing the modified MOF material and the solution containing the second polymer preferably independently include a temperature of 50 to 100°C, such as 50°C, 60°C, 70°C, 80°C, 90°C, 100°C or any value therebetween; and a time of 10 min to 2 h, such as 10 min, 30 min, 60 min, 80 min, 100 min, 120 min or any value therebetween.

[0035] The present invention also provides application of the composite bipolar membrane in the preparation of hexacyanocobaltate.

[0036] The present invention will be described in detail below through examples.

[0037] Preparation Example 1-1

[0038] Sodium styrene sulfonate and butadiene were added to trichloroethane at a molar ratio of 1:1.2, and reacted at a temperature of 50°C and a pressure of 0.5 MPa for 10 hours to obtain a sodium styrene sulfonate / butadiene copolymer. Sodium styrene sulfonate / butadiene copolymer was reacted with 2-fluoro-4-mercaptoaniline at a temperature of 70°C and a pressure of 0.5 MPa for 5 hours, the molar ratio of 2-fluoro-4-mercaptoaniline to butadiene being 1:1, to obtain a solution containing the first polymer at a concentration of 5 wt%.

[0039] Preparation Example 1-2

[0040] Sodium styrene sulfonate and butadiene were added to trichloroethane at a molar ratio of 1:0.5, and reacted at a temperature of 100° C. and a pressure of 0.1 MPa for 0.5 h to obtain a sodium styrene sulfonate / butadiene copolymer. Sodium styrene sulfonate / butadiene copolymer was reacted with 2-fluoro-4-mercaptoaniline at a temperature of 100° C. and a pressure of 0.1 MPa for 0.5 h, the molar ratio of 2-fluoro-4-mercaptoaniline to butadiene being 1:1, to obtain a solution containing the first polymer at a concentration of 2 wt%.

[0041] Preparation Example 1-3

[0042] Sodium styrene sulfonate and butadiene were added to trichloroethane at a molar ratio of 1:2, and reacted at a temperature of 80°C and a pressure of 0.3 MPa for 5 hours to obtain a sodium styrene sulfonate / butadiene copolymer. Sodium styrene sulfonate / butadiene copolymer was reacted with 2-fluoro-4-mercaptoaniline at a temperature of 80°C and a pressure of 0.3 MPa for 2 hours, the molar ratio of 2-fluoro-4-mercaptoaniline to butadiene being 1:1, to obtain a solution containing the first polymer with a concentration of 8 wt%.

[0043] Comparative Preparation Example 1-1

[0044] Sodium styrene sulfonate and butadiene were added into trichloroethane at a molar ratio of 1:1.2, and reacted for 10 hours at a temperature of 50° C. and a pressure of 0.5 MPa to obtain a reference solution containing the first polymer with a concentration of 5 wt %.

[0045] Preparation Example 2-1

[0046] Styrene and butadiene are added into trichloroethane at a molar ratio of 1:0.5, and reacted at a temperature of 50°C and a pressure of 0.5 MPa for 10 hours to obtain a styrene / butadiene copolymer; the styrene / butadiene copolymer is reacted with 3-amino-5-mercapto-1,2,4-triazole at a temperature of 70°C and a pressure of 0.5 MPa for 5 hours, the molar ratio of 3-amino-5-mercapto-1,2,4-triazole to butadiene is 1:1, and a solution containing a second polymer with a concentration of 5wt% is obtained.

[0047] Preparation Example 2-2

[0048] Styrene and butadiene are added into trichloroethane at a molar ratio of 1:1.2, and reacted at a temperature of 100°C and a pressure of 0.1 MPa for 0.5 h to obtain a styrene / butadiene copolymer; the styrene / butadiene copolymer is reacted with 3-amino-5-mercapto-1,2,4-triazole at a temperature of 100°C and a pressure of 0.1 MPa for 0.5 h, the molar ratio of 3-amino-5-mercapto-1,2,4-triazole to butadiene is 1:1, and a solution containing a second polymer with a concentration of 2 wt% is obtained.

[0049] Preparation Example 2-3

[0050] Styrene and butadiene are added into trichloroethane at a molar ratio of 1:2, and reacted at a temperature of 80°C and a pressure of 0.3 MPa for 5 hours to obtain a styrene / butadiene copolymer; the styrene / butadiene copolymer is reacted with 3-amino-5-mercapto-1,2,4-triazole at a temperature of 80°C and a pressure of 0.3 MPa for 2 hours, the molar ratio of 3-amino-5-mercapto-1,2,4-triazole to butadiene is 1:1, and a solution containing a second polymer with a concentration of 8wt% is obtained.

[0051] Comparative Preparation Example 2-1

[0052] A solution containing the second polymer was prepared according to the method of Preparation Example 2-1, except that styrene was replaced by butadiene in the same molar amount. The other conditions were the same as Preparation Example 2-1, and a reference solution containing the second polymer with a concentration of 5 wt% was obtained.

[0053] Preparation Example 3-1

[0054] S11. 5 g of 3,5-pyrazoledicarboxylic acid monohydrate was dispersed in 1 L of a 0.3 wt % sodium hydroxide aqueous solution, 10 g of aluminum chloride was added to the obtained dispersion and stirred until dissolved, and then the obtained solution was heated at 90° C. for 48 h and filtered, and the obtained precipitate was vacuum dried at 60° C. for 2 h to obtain a MOF carrier;

[0055] S12. Activate the MOF carrier at 140°C for 24 hours, then disperse the obtained activated MOF carrier with iron nitrate and copper nitrate in acetonitrile in a mass ratio of 1:0.5:0.1, then heat to 70°C and react for 24 hours. After the reaction results, cool to room temperature to obtain a solution containing modified MOF material with a concentration of 5wt%.

[0056] Preparation Example 3-2

[0057] S11. 5 g of 3,5-pyrazoledicarboxylic acid monohydrate was dispersed in 1 L of a 0.3 wt % sodium hydroxide aqueous solution, 10 g of aluminum chloride was added to the obtained dispersion and stirred until dissolved, and then the obtained solution was heated at 110° C. for 10 h and filtered, and the obtained precipitate was vacuum dried at 60° C. for 2 h to obtain a MOF carrier;

[0058] S12. Activate the MOF carrier at 160°C for 10 hours, then disperse the obtained activated MOF carrier, iron nitrate and copper nitrate in acetonitrile in a mass ratio of 1:0.8:0.3, and then heat to 60°C for reaction for 48 hours. After the reaction results, cool to room temperature to obtain a solution containing modified MOF material with a concentration of 5wt%.

[0059] Preparation Example 3-3

[0060] S11. 5 g of 3,5-pyrazoledicarboxylic acid monohydrate was dispersed in 1 L of a 0.3 wt % sodium hydroxide aqueous solution, 10 g of aluminum chloride was added to the obtained dispersion and stirred until dissolved, and then the obtained solution was heated at 100° C. for 24 h and filtered, and the obtained precipitate was vacuum dried at 60° C. for 2 h to obtain a MOF carrier;

[0061] S12. Activate the MOF carrier at 150°C for 15 hours, then disperse the obtained activated MOF carrier, iron nitrate and copper nitrate in acetonitrile in a mass ratio of 1:0.6:0.2, and then heat to 80°C for reaction for 10 hours. After the reaction results, cool to room temperature to obtain a solution containing modified MOF material with a concentration of 5wt%.

[0062] Preparation Example 3-4

[0063] A solution containing a modified MOF material was prepared according to the method of Preparation Example 3-1, except that copper nitrate was replaced by the same weight portion of ferric nitrate. The other conditions were the same as those of Preparation Example 3-1, and a solution containing a modified MOF material was obtained.

[0064] Example 1

[0065] The solution containing the first polymer (obtained from Preparation Example 1-1) is sprayed on the surface of the substrate and vacuum dried at 60°C for 2h to obtain a cation exchange membrane; the solution containing the modified MOF material (obtained from Preparation Example 3-1) is sprayed on the surface of the cation exchange membrane and vacuum dried at 60°C for 2h to obtain a MOF transition membrane; the solution containing the second polymer (obtained from Preparation Example 2-1) is sprayed on the surface of the MOF transition membrane and vacuum dried at 60°C for 2h to obtain an anion exchange membrane, and then the cation exchange membrane is peeled off from the substrate to obtain a composite bipolar membrane including a cation exchange membrane, a MOF transition membrane and an anion exchange membrane stacked in sequence, which is recorded as SM-1. Among them, the thickness of the cation exchange membrane is 30±0.5 microns, the thickness of the MOF transition membrane is 5±0.5 microns, and the thickness of the anion exchange membrane is 10±0.5 microns.

[0066] Example 2

[0067] The solution containing the first polymer (obtained from Preparation Example 1-2) is sprayed on the surface of the substrate and vacuum dried at 60°C for 2h to obtain a cation exchange membrane; the solution containing the modified MOF material (obtained from Preparation Example 3-2) is sprayed on the surface of the cation exchange membrane and vacuum dried at 60°C for 2h to obtain a MOF transition membrane; the solution containing the second polymer (obtained from Preparation Example 2-2) is sprayed on the surface of the MOF transition membrane and vacuum dried at 60°C for 2h to obtain an anion exchange membrane, and then the cation exchange membrane is peeled off from the substrate to obtain a composite bipolar membrane including a cation exchange membrane, a MOF transition membrane and an anion exchange membrane stacked in sequence, which is recorded as SM-2. Among them, the thickness of the cation exchange membrane is 30±0.5 microns, the thickness of the MOF transition membrane is 5±0.5 microns, and the thickness of the anion exchange membrane is 10±0.5 microns.

[0068] Example 3

[0069] The solution containing the first polymer (obtained from Preparation Example 1-3) is sprayed on the surface of the substrate and vacuum dried at 60°C for 2h to obtain a cation exchange membrane; the solution containing the modified MOF material (obtained from Preparation Example 3-3) is sprayed on the surface of the cation exchange membrane and vacuum dried at 60°C for 2h to obtain a MOF transition membrane; the solution containing the second polymer (obtained from Preparation Example 2-3) is sprayed on the surface of the MOF transition membrane and vacuum dried at 60°C for 2h to obtain an anion exchange membrane, and then the cation exchange membrane is peeled off from the substrate to obtain a composite bipolar membrane including a cation exchange membrane, a MOF transition membrane and an anion exchange membrane stacked in sequence, which is recorded as SM-3. Among them, the thickness of the cation exchange membrane is 30±0.5 microns, the thickness of the MOF transition membrane is 5±0.5 microns, and the thickness of the anion exchange membrane is 10±0.5 microns.

[0070] Example 4

[0071] A composite bipolar membrane was prepared according to the method of Example 1, except that the solution containing the modified MOF material obtained in Preparation Example 3-1 was replaced by the solution containing the modified MOF material obtained in Preparation Example 3-4 in the same weight portion, and the other conditions were the same as in Example 1 to obtain a composite bipolar membrane, which was recorded as SM-4. Among them, the thickness of the cation exchange membrane was 30±0.5 microns, the thickness of the MOF transition membrane was 5±0.5 microns, and the thickness of the anion exchange membrane was 10±0.5 microns.

[0072] Comparative Example 1

[0073] A composite bipolar membrane was prepared according to the method of Example 1, except that the solution containing the first polymer obtained in Preparation Example 1-1 was replaced by the reference solution containing the first polymer obtained in Comparative Preparation Example 1-1 in the same weight portion, and the other conditions were the same as in Example 1 to obtain a reference composite bipolar membrane, which was recorded as DSM-1. The thickness of the cation exchange membrane was 30±0.5 microns, the thickness of the MOF transition membrane was 5±0.5 microns, and the thickness of the anion exchange membrane was 10±0.5 microns.

[0074] Comparative Example 2

[0075] A composite bipolar membrane was prepared according to the method of Example 1, except that the solution containing the second polymer obtained in Preparation Example 2-1 was replaced by the reference solution containing the second polymer obtained in Comparative Preparation Example 2-1 in the same weight portion, and the other conditions were the same as in Example 1 to obtain a reference composite bipolar membrane, which was recorded as DSM-2. The thickness of the cation exchange membrane was 30±0.5 microns, the thickness of the MOF transition membrane was 5±0.5 microns, and the thickness of the anion exchange membrane was 10±0.5 microns.

[0076] Test Case

[0077] This test example uses a two-compartment bipolar membrane electrodialysis device, the anode plate material is a mesh metal DSA, the cathode plate material is a mesh titanium electrode plate, the bipolar membrane and cation exchange membrane are BP-1 bipolar membrane and CMX cation exchange membrane ( CMX, ASTOM, Japan), membrane area 200cm 2 The membrane stack is composed of 5 groups of repeating units of B1C2 configuration.

[0078] A potassium hexacyanocobaltate solution with a concentration of 6.5 wt % was introduced into the acid chamber inlet of the two-compartment bipolar membrane electrodialysis device, and deionized water was introduced into the alkali chamber. A DC power supply was turned on for constant voltage 8 V electrodialysis. After 30 min, the concentration of hexacyanocobaltate at the acid chamber outlet was measured. The results are shown in Table 1.

[0079] After the bipolar membrane was continuously used for electrodialysis to prepare hexacyanocobalt acid for half a year, the concentration of hexacyanocobalt acid at the outlet of the acid chamber after the electrodialysis was completed was determined according to the above method. The results are shown in Table 1.

[0080] Table 1

[0081] Bipolar membrane When just running After half a year of operation SM-1 4.8wt% 4.6wt% SM-2 5.2wt% 5.1wt% SM-3 4.9wt% 4.9wt% SM-4 4.0wt% 3.9wt% DSM-1 3.8wt% 1.6wt% DSM-2 3.6wt% 1.5wt%

[0082] From the results of Examples 1 to 4 and Comparative Examples 1 to 2, it can be seen that the composite bipolar membrane provided by the present invention can be used for the production of hexacyanocobalt acid by bipolar membrane electrodialysis to continuously and efficiently obtain hexacyanocobalt acid. From the comparison between Example 1 and Example 4, it can be seen that when the MOF material is co-modified with Fe and Cu, it is more conducive to promoting the synthesis of hexahydrocobalt acid.

[0083] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. A person skilled in the art may change, modify, replace and modify the above embodiments within the scope of the present invention without departing from the principles and purpose of the present invention.

Claims

1. A composite bipolar membrane, characterized in that: The composite bipolar membrane comprises a cation exchange membrane, a MOF transition membrane and an anion exchange membrane stacked in sequence; the cation exchange membrane is formed by a first polymer, which is a random copolymer having a structure represented by formula (1); the anion exchange membrane is formed by a second polymer, which is a random copolymer having a structure represented by formula (2); m and n represent the molar proportions of the two structural units in formula (1), and the ratio of m to n is 1:(0.5-2); p and q represent the molar proportions of the two structural units in formula (2), and the ratio of p to q is 1:(0.5-2);.

2. The composite bipolar membrane according to claim 1, characterized in that: The thickness of the cation exchange membrane is 10 to 60 micrometers, the thickness of the MOF transition membrane is 1 to 10 micrometers, and the thickness of the anion exchange membrane is 5 to 20 micrometers.

3. The composite bipolar membrane according to claim 1, characterized in that: The first polymer is prepared by the following method: sodium styrene sulfonate and butadiene are added into an organic solvent at a molar ratio of 1:(0.5-2) to carry out a first copolymerization reaction, and then the obtained sodium styrene sulfonate / butadiene copolymer is subjected to a first thiol-ene click reaction with 2-fluoro-4-mercaptoaniline to obtain a solution containing the first polymer; Preferably, the conditions of the first copolymerization reaction include a polymerization temperature of 50 to 100° C., a polymerization pressure of 0.1 to 0.5 MPa, and a polymerization time of 0.5 to 10 h; Preferably, the molar ratio of butadiene to 2-fluoro-4-mercaptoaniline is (0.9-1.1):1; Preferably, the conditions of the first thiol-ene click reaction include a temperature of 70 to 100° C., a pressure of 0.1 to 0.5 MPa, and a time of 0.5 to 5 h.

4. The composite bipolar membrane according to claim 1, characterized in that: The second polymer is prepared by the following method: styrene and butadiene are added into an organic solvent at a molar ratio of 1:(0.5-2) to carry out a second copolymerization reaction, and then the obtained styrene / butadiene copolymer is subjected to a second thiol-ene click reaction with 3-amino-5-mercapto-1,2,4-triazole to obtain a solution containing the second polymer; Preferably, the conditions of the second copolymerization reaction include a polymerization temperature of 50 to 100° C., a polymerization pressure of 0.1 to 0.5 MPa, and a polymerization time of 0.5 to 10 h; Preferably, the molar ratio of butadiene to 3-amino-5-mercapto-1,2,4-triazole is (0.9-1.1):1; Preferably, the conditions of the second thiol-ene click reaction include a temperature of 70 to 100° C., a pressure of 0.1 to 0.5 MPa, and a time of 0.5 to 5 h.

5. The composite bipolar membrane according to claim 1, characterized in that: The MOF transition film is formed by a modified MOF material, and the modified MOF material is a MOF material co-modified by Fe and Cu.

6. The composite bipolar membrane according to claim 5, characterized in that: The modified MOF material is prepared according to the following method: S11. 3,5-pyrazoledicarboxylic acid is dispersed in an alkaline solution, aluminum chloride is added to the obtained dispersion and stirred until dissolved, and then the obtained solution is heated at 90 to 110° C. for 10 to 48 hours and filtered, and the obtained precipitate is dried to obtain a MOF carrier; S12. Activate the MOF carrier at 140-160° C. for 10-24 h, disperse the activated MOF carrier with ferric nitrate and copper nitrate in an organic solvent, heat to 60-80° C. for reaction for 10-48 h, wait for the reaction result, and cool to room temperature to obtain a solution containing a modified MOF material; Preferably, the mass ratio of the MOF carrier, ferric nitrate and copper nitrate is 1:(0.5-0.8):(0.1-0.3).

7. The method for preparing a composite bipolar membrane according to any one of claims 1 to 6, characterized in that: The method comprises the following steps: S21. sodium styrene sulfonate and butadiene are added to an organic solvent at a molar ratio of 1:(0.5-2) to carry out a first copolymerization reaction, and then the obtained sodium styrene sulfonate / butadiene copolymer is subjected to a first thiol-ene click reaction with 2-fluoro-4-mercaptoaniline to obtain a solution containing a first polymer; Styrene and butadiene are added into an organic solvent at a molar ratio of 1:(0.5-2) to carry out a second copolymerization reaction, and then the obtained styrene / butadiene copolymer is subjected to a second thiol-ene click reaction with 3-amino-5-mercapto-1,2,4-triazole to obtain a solution containing a second polymer; S22. Spray a solution containing the first polymer on the surface of the substrate and dry it to obtain a cation exchange membrane layer; spray a solution containing the modified MOF material on the surface of the cation exchange membrane and dry it to obtain a MOF transition membrane; spray a solution containing the second polymer on the surface of the MOF transition membrane and dry it to obtain an anion exchange membrane.

8. The method for preparing a composite bipolar membrane according to claim 7, characterized in that: The concentrations of the solution containing the first polymer, the solution containing the second polymer, and the solution containing the modified MOF material are each independently 0.1 to 10 wt %.

9. The method for preparing a composite bipolar membrane according to claim 7, characterized in that: The conditions for drying the solution containing the first polymer, the solution containing the modified MOF material and the solution containing the second polymer independently include a temperature of 50 to 100° C. and a time of 10 minutes to 2 hours.

10. Use of the composite bipolar membrane according to any one of claims 1 to 6 in the preparation of hexacyanocobaltic acid.

Citation Information

Patent Citations

  • Bipolar membrane containing MOF (Metal Organic Framework) catalyst middle layer as well as preparation method and application of bipolar membrane

    CN118286869A

  • Polyarylene ether compound containing sulfonic acid group, composition containing same, and method for manufacturing those

    CN1703443A

  • Production of acid

    JP1993184877A

  • Method for producing cation exchange membrane

    JP2012001621A

  • Bipolar membrane

    JP2020097648A